Composição e diversidade de espécies da anurofauna da Estação Científica Ferreira Penna, Floresta Nacional de Caxiuanã, Pará, Brasil - BERNARDI, José Antônio Renan (Universidade Federal do Pará, 2013)
This study compares the composition of the anurofauna of the four principal habitats (terra firme forest, capoeira, igapô and aquatic vegetation) in the areas of two black water streams (igarapé Arauá and Laranjal), at the "Ferreira Penna Scientific Station" (Estação Científica Ferreira Penna (ECFPn)), located in the "Caxiuanã National Forest (FLONA de Caxiuanã)", Pará, Brazil. The samples of the areas were conduct using transects measuring 850 m in length and 10 m in width. Both areas were studied in the four periods of the year and related to annual rainfall seasonality (period of transition rainy/dry season, dry season, transition dry/rainy season, and rainy season). Shannon-Weiner índex of diversity and Jaccard index of similarity were used to compare the two areas and the habitats. Samples of anurans totalled 924 individuais belonging to 29 species distributed in 15 genera and 5 families. Hylidae was the most abundant, followed by Leptodactylidae, Dendrobatidae, Bufinidae and Pipidae. Terra firme forest showed the highest diversity. The number of species recorded was highest in the rainy season. This study and those of Ávila-Pires and Hoogmoed (1997) indicate a total of 41 species of frogs for this region, a quite high number for eastern Amazonia, reinforcing the hypothesis that the low diversity of the species of frogs normally related to this region is at least partially a result of the low number of herpetological inventories carried out up to now.